The role of television in the enhancement of farmers' agricultural knowledge - Nazari, Mohammed Reza; Hassan, Md. Salleh (Academic Journals, 2011)
The purpose of this study was to evaluate the role of television as an educational tool to the enhancement of farmers’ knowledge. This study was a randomized subject, pretest-posttest design among farmers who were working and residing in Kohgiluyeh va Buyer Ahmad province, Iran. The subjects of the study included 161 farmers who were selected randomly from rural areas. After determining the educational goals of the study, a questionnaire was designed as pre and post test. Based on educational contents, one TV program was produced with emphasis on fighting against agricultural pests, and correct method of using agricultural poisons. Participants responded to the pre and post test before and after broadcasting the television program through the provincial broadcast center. Almost all farmers in this study were male (90.1%) and married (80%) with mean age of 41.65 ± 14.69 years. The finding of the study showed that educational intervention through a TV program resulted in a significant knowledge enhancement from 3.73 to 6.26 (p<0.001). Mass media offer effective channels for communicating agricultural messages, which can increase knowledge and influence behavior of audience members.